TUVA TÜRKLERİNİN DESTANLARINDAN TAHTACI TÜRKMENLERİN ADETLERİNE: BAŞ YÜLÜME - Kizildağ, Hasan (Motif Akademi Halk Bilimi Dergisi, 2024)
Turkish culture has been in motion and has been in continuity from the archaic times of history to modern times. Turks, who have migrated to different regions from Altai to Anatolia and the Balkans on the east-west, north-south axis, exhibit a cultural integrity even if they are subject to different religions and sects. For this reason, the monitoring and identification of cultural elements should be carried out from this perspective. One of the most important elements of this cultural unity is the commonalities in transition period practices. In this study, the practices called “baş yülüme/head shaving” of Tuvan Turks and Tahtacı Turkmens living in Anatolia were mutually analyzed. The forms in which Tahtacı Turkmens perform the “baş yülüme” practice, which is included in the transitional period practices of Tuvan Turks and reflected in Tuvan epics, are discussed with examples. Within the scope of the study, it has been determined that the “baş yülüme” tradition of Tuvan Turks and the practice of Tahtacı Turkmens, which has a religious character, have many similarities. It is thought that the elements found as a result of the comparison of the samples taken from Tuvan epics with the compilations made from Tahtacı Turkmens will set an example in terms of showing that Turkish culture has a continuity despite the changes in geography and religion. In addition, in this study, it has been determined that a practice belonging to the Tuvan Turks under the influence of Shamanism and Lamaism is also continued with certain differences among Tahtacı Turkmens in Anatolia.